Status of iodine nutrition among pregnant women attending antenatal clinic of a secondary care hospital: A cross-sectional study from Northern India - Shashi Kant; Partha Haldar; Ayush Lohiya; Kapil Yadav; Chandrakant S Pandav (Wolters Kluwer Medknow Publications, 2017)
Background: Daily requirement of iodine increases during pregnancy making pregnant women a high-risk group for iodine deficiency disorders. The limited available literature shows that even in iodine sufficient population, pregnant women are iodine deficient. Objective: The objective of this study is to assess the current iodine nutrition status among pregnant women in Ballabgarh, district Faridabad, Haryana. Materials and Methods: Pregnant women were recruited from antenatal clinic (ANC) of subdistrict hospital (SDH), Ballabgarh, Haryana. Consecutive sampling strategy was followed to recruit pregnant women, and women of all trimesters were included in the study. Urinary iodine estimation was done using simple microplate method, and salt iodine was estimated using iodometric titration. The study was approved by Institute Ethics Committee, All India Institute of Medical Sciences (AIIMS), New Delhi. Results: Out of the total 1031 pregnant women, 90.9% were using adequately iodized salt. Median (interquartile range [IQR]) salt consumption by the pregnant women was 8.3 (6.7, 11.1) g/day. Median (IQR) urinary iodine concentration (UIC) for the pregnant women was 260 (199, 323) μg/L. Only 13.5% of pregnant women had insufficient iodine intake (UIC <150 μg/L). There was no significant difference in median UIC values by household salt iodine content and across three trimesters of pregnancy. Conclusion: Iodine nutrition status of the pregnant women attending ANC clinic of SDH Ballabgarh was adequate with attainment of universal salt iodization goal of> 90% adequately iodized salt coverage in the study population.